Reunification of Germany and Perceptions of its History (Czech Journal of International Relations, 2002)
Richard J. Evans: Rereading German History /1800-1996 From Unification to Reunification/. Routledge, London/New York 1997, 256 stran, ISBN 0-415-15900-8.